Views of Assessors on the Role of Awards in Creating and Sustaining a Culture of Excellence - Ahmed Alkhawaldeh, Khleef (Jordan Journal of Business Administration, 2023)
This research paper aimed to clarify the assessors’ views on the role of awards in creating and sustaining a culture of excellence in the institutions and companies participating in the competition for winning excellence awards. It also aimed to reveal the perspectives of excellence assessors concerning the relationship between the impact of excellence awards on each of the three pillars of excellence (shaping the future and agility, alignment and integration and sustainable performance) and on creating and sustaining a culture of excellence. Outputs of one-sample T-test indicated that the impacts of excellence awards on future shaping and agility and alignment and integration are slightly below the moderate level. Outputs of one-sample T-test also indicated that the impacts of excellence awards on sustainable performance and creating and sustaining a culture of excellence are not statistically different from the moderate level. Results of correlation and regression tests supported the statistically significant relationships between the impacts of excellence awards on each of the three excellence pillars and on creating and sustaining a culture of excellence. The research concluded that building a culture of excellence is the right approach for continual improvement to achieve and sustain future success and business continuity.